INFORMATION SYSTEMS DESIGN AND IMPLEMENTATION PROBLEMS ON UNIVERSITY EXAM - Rahayu Noveandini (Majalah SIKOMTEK, 2010)
Various efforts have been undertaken by universities to improve academic quality control. This effort is intended to improve the quality of education. Evaluation of the monitoring process is carried out continuously and continuous in the end will be able to fix the quality of education. One of the efforts is to build information systems design exam. With the availability of information systems exam is expected that users can perform a variety of analysis and also can provide a more accurate exam. Development of information system design is intended as a first step in increasing the academic quality of universities.